Determination Of Bond Angles And Torsion Angles Of Systemic Fungicide (N-(2, 6 Dim Ethyl Phenyl)-N-(2-Keto-1-Methyl Butyl) 3-Hydroxypropanamide) - DR. JYOTSNA CHAUHAN (International Journal of Pharma and Bio Sciences, 2012)
structure based functional studies to aid the development of effective therapeutic agents and drugs. Crystallography can reliably provide the answer to many structure related questions, from global folds to atomic details of bonding. The activity of fungicides is intimately related to its chemical structure. Knowledge about the chemical structure of a chemical is useful for the synthesis of new compounds with more specific actions and fewer adverse reactions, to increase/decrease the duration of action of the original drug or to get a more potent compound, to restrict the action to a specific system of the body and to reduce the adverse reactions, toxicity and other disadvantages associated. We can understand the basic chemical groups responsible for drug action].The composition of the crystal (N-(2,6 dim ethyl phenyl)-N-(2-keto-1-methyl butyl) 3- hydroxypropanamide) is confirmed by comparing the infra-red spectra of the two components. The unit cell parameters were determined by directly automatic computerized 4-circled Enraf Nonious CAD-4 Diffractometer in the w-2q scan mode using graphite filtered Moka radiation. These data showed a =7.865(1) Å, b =13.122(2) Å, c =15.130(1) Å, a =90(1)o, b=101.75(2)o, g=90(1)o. The space group was determined to be P21/c. The calculated density of the crystal is 1.1919g/cm3]and measured density is 1.192g/cm3.All the lengths in the Benzene ring vary from 1.3705(2)Å to 1.4176(1)Å, show a good agreement with their standard value of 1.395Å. The deviations of the inner bond angles in the Benzene ring from 120º are slightly greater than 2s (=0.7º).The geometry around N(1), C(13) and C(10) appears to be normal as all the lengths are close to single bond normal values and the angles are according to the configuration. The C-N distances are similar to that observed in structures having triagonal hybridization.